2017
DOI: 10.4172/2155-6148.1000718
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation in the Intensive Care Unit: A Prospective Study of Indications and Factors that Affect Outcome in a Tertiary Hospital in Nigeria

Abstract: The need for ventilatory support is one of the commonest indications for admission into the intensive care unit (ICU). Despite the usefulness of mechanical ventilation, its damaging effect on the lungs has also been widely recognized.The study was a prospective, case-controlled survey of all mechanically ventilated patients admitted in our ICU from November 2013 to April 2014. For every ventilated patient, a non-ventilated similar patient served as a control.A total of 128 patients were admitted into the ICU o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
3
4
1
Order By: Relevance
“…This low ventilatory rate in our ICU could be due to inadequate availability of ventilators, setup difference, the number of ICU and number of patients. In contrast our result is higher than from studies conducted in Mekelle, Egypt, Nigeria and Mumbai reported by 36.7%, 40%, 34.4%, and 34.5% respectively (7,9,12,18,19). This difference may be due to our study was conducted in tertiary hospital which served for variety of patients referred from different region of the country.…”
Section: Discussioncontrasting
confidence: 81%
“…This low ventilatory rate in our ICU could be due to inadequate availability of ventilators, setup difference, the number of ICU and number of patients. In contrast our result is higher than from studies conducted in Mekelle, Egypt, Nigeria and Mumbai reported by 36.7%, 40%, 34.4%, and 34.5% respectively (7,9,12,18,19). This difference may be due to our study was conducted in tertiary hospital which served for variety of patients referred from different region of the country.…”
Section: Discussioncontrasting
confidence: 81%
“…The report from different published study shows 34% in Brazil, 42.1% in central India, 67.21% in western India, 31.8% in Nigeria, 64% in Egypt, 73.5% in Uganda and 28.6% in Ayder Hospital, Ethiopia. 5,6,11,15,16,18,19 Our findings were almost the same as the study conducted by Chiwhane and Diwan, which reported 42.1%. On other hand, our finding was higher than the studies conducted in Brazil (34%), Nigeria (31.8%), and Ayder Hospital, Ethiopia (28.6%).…”
Section: Discussionsupporting
confidence: 90%
“…This finding was in line with other published studies in India, Chile, Nigeria, and Ethiopia, which ranged from 38.6% to 86.07%. 5 , 9 , 11 , 16 Nevertheless, the study conducted in Cairo prevails cardiac disease as the predominant indication of mechanical ventilation. This discrepancy in indication might be due to the type of intensive care unit and the difference in the category of diseases in the setting.…”
Section: Discussionmentioning
confidence: 99%
“…Te continuous development of mechanical ventilators and their clinical use have been critical factors for the development and growth of critical care and respiratory professions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilator support is one of the main indications for admission to the intensive care unit (ICU). The continuous development of mechanical ventilators and their clinical use have been critical factors for the development and growth of critical care and respiratory professions [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%